The Effectiveness of Zakat Disbursement at the National Board of Zakat (Baznas) Kendal Regency - Bahri, Efri Syamsul; Aslam, Mohd Mizan Mohammad; Mubarok, Abdullah (Journal of Multi-Disciplines Science, 2023)
Zakat has a significant role in improving people's welfare. One entity that manages Zakat for the community's welfare is the Kendal Regency National Amil Zakat Agency (Baznas). This study aims to measure the level of effectiveness of Zakat disbursement at the Baznas Kendal Regency. This research was conducted using quantitative methods. The data is sourced from the Kendal Regency Baznas Financial Report for 2020-2022. Disbursement effectiveness measurement uses the allocation-to-collection ratio (ACR) approach. In addition, this study uses a descriptive approach. The results showed that the ACR value was 108 per cent. Thus, the level of effectiveness of Kendal Regency Baznas disbursement is in the Highly Effective category. Kendal Regency Baznas needs to optimize the disbursement of Zakat to Mustahiq, which covers five program areas: Education, Economy, Health, Da'wah, and Humanity.